Measuring Socioeconomic Position From The Social Inequalities In Health Perspective?: The Case of Costa Rica - Fantin, Romain Clement (2019)
Introduction: Measuring socioeconomic position (SEP) is central in the analysis of social inequalities in health (SIH). It requires the use of updated instruments, adapted to a particular conceptual framework, taking into account the local context and the population characteristics. This study aims to present and discuss the advantages and disadvantages of different measurement of SEP used in Costa Rica for the analysis of health inequalities. Materials and methods: A systematic review of the existing instruments and methods used to characterize SEP in Costa Rica was carried out. Results: There is a great diversity of instruments used as proxies of SEP in Costa Rica, both at the individual, and at geographical level. These measures allow to capture specific dimensions of SEP potentially associated with different health outcomes. Being a latent concept, variables approaching SEP should refer to their specific conceptual framework, be adapted to the study design, and population’s characteristics (e.g. age), and should consider the study feasibility of data collection. Due to the variety and different conceptual frameworks behind each SEP variable, it is not possible to establish the existence of a gold standard. Conclusion: This review of the Costa Rican health inequalities literature regarding SEP instruments, can contribute to a better use of the existing tools. It will allow researchers to better evaluate the instruments that have been previously validated, their respective theoretical frameworks and limitations, to choose the most suitable proxy of SEP for the local context analyzed.